Data associated with "Atmospheric water recycling an essential feature of critical natural asset stewardship" - Keys, Patrick (Colorado State University. Libraries, 2022)
Global ecosystems are interconnected via atmospheric water vapor flows. Land use change can modify evaporation from land, altering atmospheric moisture recycling and potentially leading to significant changes in downwind precipitation and associated ecological impacts. We combine insights on global ecosystem-regulated moisture recycling with an analysis of critical natural assets (CNA, the 30% of global land providing most of nature’s contributions to people) to reveal the sources and sinks of atmospheric water cycle regulation. We find that 65% of the precipitation over CNA is supplied by evaporation from other land areas. Likewise, CNA regions supply critical moisture as precipitation to terrestrial natural ecosystems and production systems worldwide, with 44% of CNA evaporation falling on terrestrial surfaces. Specifically, the Congo River basin emerges as a hotspot of overlap between local atmospheric water cycle maintenance and concentration of nature’s contributions to people. Our results suggest global priority areas for conservation efforts beyond and in support of CNA, emphasizing the importance of sparsely populated managed forests and rangelands, along with wild forests, for fostering moisture recycling to and within CNA. This work provides additional insights for understanding the manifold benefits associated with achieving SDG 15, to sustainably manage life on land and conserve biodiversity.
This dataset include moisture recycling data (tracked evaporation, total evaporation, and total precipitation) derived from ERA-Interim archive data produced by the European Centre for Mesoscale Weather Forecasting, using the Water Accounting Model 2 layers model (https://doi.org/10.5281/zenodo.6029408). The data span nearly the entire planet, excluding the Antarctic continental region in the south and the extreme Arctic in the north. Additional data include the regional files corresponding to the specific CNA regions that we analyzed, a set of ERA-Interim constant data, and a data file containing the upscaled Anthrome data. School of Global Environmental Sustainability
Keywords: moisture recycling; ecosystem services; water; conservation; forests; rangelands; sustainable development goals